Akutyalipszis most: a Covid-19 és a kutyizmus - Csonka , Berta (Kultúratudományi Szemle, 2022)
Doglypse now: the relationships between Covid-19 and dogism Berta Csonka This essay investigates the changes caused by the COVID-19 pandemic with regard to the human-dog relationship and outlines a possible apocalyptic view, where relationship between human and dog is considered to be more acceptable than the relationship between humans. Such a phenomenon would support the theory of Dogism, created and researched by the author.